2005
DOI: 10.2190/crk0-cbn7-qeve-xwpg
|View full text |Cite
|
Sign up to set email alerts
|

The Factor Structure of a Chinese Version of the Geriatric Depression Scale

Abstract: The findings in this study presented evidence for the applicability of the GDS to older Chinese-Canadians. This instrument would be useful for practitioners to identify potential depression concerns among older adults in this ethnic community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
(28 reference statements)
3
16
0
1
Order By: Relevance
“…Both similarities and differences can be found when these four factors are compared with those identified in previous studies on older Chinese in other jurisdictions. Although positive mood and negative mood are combined as one factor in this study, they are consistent with those identified by Mui (1996) and Lai et al (2005). The factors related to inferiority and disinterest identified in this study are also consistent with those identified by Lai and associates on the depressive symptoms of the aging Chinese in Canada.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Both similarities and differences can be found when these four factors are compared with those identified in previous studies on older Chinese in other jurisdictions. Although positive mood and negative mood are combined as one factor in this study, they are consistent with those identified by Mui (1996) and Lai et al (2005). The factors related to inferiority and disinterest identified in this study are also consistent with those identified by Lai and associates on the depressive symptoms of the aging Chinese in Canada.…”
Section: Discussionsupporting
confidence: 89%
“…(2) Using the second sample (n ¼ 114), confirmatory factor analysis was conducted to examine whether the initial factor structure identified through exploration factor analysis would achieve a goodness-of-fit with the data in the second sample and the significance of individual factor loadings. This method of randomly assigning a larger sample into two independent samples is a common approach (Lai et al, 2005;Lane et al, 1999;Miller, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() and Lai et al . () used area probability sampling involving selection of census tracks and city blocks, and their sample sizes were 407 and 2,272, respectively. Finally, Lai () recruited his participants through randomly selecting names from the membership list from a Chinese seniors' center, whose members accounted for more than 77% of the estimated older Chinese population in that area.…”
Section: Resultsmentioning
confidence: 99%
“…The neurologists made their evaluation at a regular inclinic follow-up visit and applied the Hoehn and Yahr staging (HY), the PSQI [12], the ESS [13], the Geriatric Depression Scale (GDS)-30 items [14,15], and the Hamilton Anxiety Scale (HAMA) [16]. A retest evaluation was carried out on 17 patients 4 weeks after the first assessment.…”
Section: Methodsmentioning
confidence: 99%